1997
DOI: 10.1002/(sici)1097-0177(199703)208:3<326::aid-aja4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

In situ localization of thrombospondin-1 and thrombospondin-3 transcripts in the avian embryo

Abstract: Two novel cDNA probes to chicken thrombospondin‐1 (TSP‐1) and TSP‐3 were used to determine by in situ hybridization the origins of these extracellular matrix proteins during embryogenesis. Both TSP‐1 and TSP‐3 are expressed in embryonic cartilage. TSP‐1 expression is limited to early chondrocytes, in contrast to TSP‐3 mRNAs that are found in older proliferative and hypertrophic chondrocytes. TSP‐1 and TSP‐3 are expressed consecutively during neurogenesis as well, with the TSP‐1 probe hybridizing in proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 25 publications
7
66
0
Order By: Relevance
“…46 In contrast, lower Mr isoforms (Tn190/200) are observed to be expressed more stably in dense connective tissue in areas such as gizzard tendons, intramuscular connective tissue, aortic mesenchyme, articular cartilage, inner layer of perichondrium and zones of active chondrocyte proliferation, where cell condensation and differentiation are more prevalent. 22,39,41,[44][45][46][47][50][51][52] Similar patterns of tenascin-C expression are observed in mice and rats, although significantly less is known about the presence of alternatively spliced tenascin-C during human fetal development. WB and real-time PCR (RT-PCR) techniques revealed that smaller Mr tenascin-C variants are the predominant isoforms expressed in E14 mouse gut mesenchyme, 53 and in the developing thymus and skin from E17 to P6 respectively.…”
Section: Tenascin-c Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…46 In contrast, lower Mr isoforms (Tn190/200) are observed to be expressed more stably in dense connective tissue in areas such as gizzard tendons, intramuscular connective tissue, aortic mesenchyme, articular cartilage, inner layer of perichondrium and zones of active chondrocyte proliferation, where cell condensation and differentiation are more prevalent. 22,39,41,[44][45][46][47][50][51][52] Similar patterns of tenascin-C expression are observed in mice and rats, although significantly less is known about the presence of alternatively spliced tenascin-C during human fetal development. WB and real-time PCR (RT-PCR) techniques revealed that smaller Mr tenascin-C variants are the predominant isoforms expressed in E14 mouse gut mesenchyme, 53 and in the developing thymus and skin from E17 to P6 respectively.…”
Section: Tenascin-c Domainmentioning
confidence: 99%
“…38,39 High Mr variants (Tn230/200) were associated with regions of active tissue remodeling, cell migration and cell division; evidenced by their presence in epithelial substratum for migrating neurons, embryonic skin fibroblasts, whole brain, cerebellum, chord glia, Bergmann glia, endoderm-derived epithelium at developing lung bronchioles, growing wing bud tips, base of feather buds, major blood vessel endothelium, kidney, lung, osteoblasts and regions of osteogenesis; where the expression of tenascin-C is only required transiently. 22,34,[40][41][42][43][44][45][46][47][48][49] In these regions, large Mr tenascin-C is expressed by migrating glia and Bergmann glia in the developing chick spinal chord and cerebellum respectively; expression in the latter of which facilitates granule cell migration. 46 In contrast, lower Mr isoforms (Tn190/200) are observed to be expressed more stably in dense connective tissue in areas such as gizzard tendons, intramuscular connective tissue, aortic mesenchyme, articular cartilage, inner layer of perichondrium and zones of active chondrocyte proliferation, where cell condensation and differentiation are more prevalent.…”
Section: Tenascin-c Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A). Periods of increased axonal growth in the developing CNS have been closely correlated with expression of large but not small tenascin-C (Crossin et al, 1989;Tucker, 1993), suggesting that fnA-D might stimulate neuronal growth during embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A diverse but restricted spatio-temporal distribution, that it is different from that described for any other extracellular matrix protein, has been reported for tenascin-C in soft and mineralised tissues (Carter et al, 1991;Tucker, 1993). Increased tenascin-C expression has been observed in many examples of tissue morphogenesis and cell migration (Luomanen and Virtanen, 1993;Julian et al, 1994;Shrestha et al, 1995).…”
mentioning
confidence: 99%